Analysis of Early Warning Systems for Emergency Situations That May Occur During the Transportation of Dangerous Goods by Rail Transport - Abdazimov, Sh. X.; Nurmamatov, Sh.R.; Zukhriddinov, Kh.K.; Normoxmatov, B.Sh. (Academia Open, 2026)
General Background The transportation of dangerous goods by rail is essential for industrial development but involves significant safety risks. Specific Background Early warning systems are designed to monitor conditions and detect abnormalities in railway operations involving hazardous materials. Knowledge Gap Despite technological advancements, there remains limited integrated analysis of system components, operational principles, and their role in emergency prevention. Aims This study aims to analyze early warning systems used in railway transport of dangerous goods, focusing on their structure, functionality, and contribution to risk reduction. Results The findings indicate that systems combining sensor technologies, real-time data transmission, analytical software, and human–machine interfaces enable timely detection of irregularities such as leaks, overheating, and mechanical failures. Integrated systems improve situational awareness and support coordinated emergency responses. Novelty The study highlights the importance of system integration and the application of digital technologies, including predictive analytics, in strengthening monitoring capabilities. Implications These results suggest that continuous development of interoperable and data-driven early warning systems is crucial for improving railway safety, minimizing environmental damage, and supporting effective emergency management. Keywords: Dangerous Goods, Railway Safety, Early Warning Systems, Monitoring Technologies, Risk Management Key Findings Highlights Integrated monitoring structures support early detection of critical operational anomalies Real-time communication systems enable coordinated emergency response actions Digital analytics contributes to improved prediction of potential failures